2016
DOI: 10.1016/j.jco.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Lp- and Sp,qr

Abstract: We study the local discrepancy of a symmetrized version of the well-known van der Corput sequence and of modified two-dimensional Hammersley point sets in arbitrary base b. We give upper bounds on the norm of the local discrepancy in Besov spaces of dominating mixed smoothness S r p,q B([0, 1) s ), which will also give us bounds on the L p -discrepancy. Our sequence and point sets will achieve the known optimal order for the L p -and S r p,q B-discrepancy. The results in this paper generalize several previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In the case d = 1 this result has been recently shown in [19,Theorem 1] which is based on the symmetrized van der Corput sequence.…”
Section: Besov and Triebel-lizorkin Spaces With Dominating Mixed Smoosupporting
confidence: 54%
“…In the case d = 1 this result has been recently shown in [19,Theorem 1] which is based on the symmetrized van der Corput sequence.…”
Section: Besov and Triebel-lizorkin Spaces With Dominating Mixed Smoosupporting
confidence: 54%
“…A generalization of this result to van der Corput sequences in arbitrary base b ≥ 2 has been shown quite recently by Kritzinger [28]. See also the recent survey article [22] and the references therein for more information about symmetrized van der Corput sequences.…”
Section: Introductionmentioning
confidence: 59%
“…In [11] it was shown that the same conditions are also sufficient and necessary for L p (R Σ b,n ) = O( √ log N /N) for all p ∈ [1, ∞). There are also some known facts on the symmetrized point sets as introduced in Definition 1.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 97%